The damselfish year - Osborne, Jordan, author; Dungy, Camille T., advisor; Beachy-Quick, Dan, committee member; Bunn, David, committee member (Colorado State University. Libraries, 2021)
This collection of poetry centers on exploring the relationship an individual has with their body and how it can be changed by the trauma of sexual violence. By refracting the self or creating a mask to obscure the self via the motif of the mermaid, the speaker of these poems endeavors to find a way to both distance herself from the trauma she has endured and bring herself closer to it in a less painful way. By doing so, the speaker is able to become a multiplicity in which the boundaries between Self and Other are blurred; pronouns that normally differentiate between actors and recipients, between individual bodies and beings, are confused and worn down by the breaking of boundaries that occurs during a violent encounter. The collection also considers questions of guilt, shame, and responsibility—incorporating figures such Mary I of England to create a space of haunting as a way to understand one's relationship to themselves and their decisions, particularly the ways in which they have been harmful to others. Other adjacent concerns here include victim blaming, violent family dynamics, ocean acidification and plastic refuse, and sex trafficking on porn websites. The collection also includes a series of loosely-structured sonnets centered on the Tarot, which is used to explore ideas of fate in relation to violence and violent histories both personal and societal. Throughout, questions of meaning and intention are brought to bear in a bodily way with the hope of asking readers to more carefully attend to how they are both liable for the perpetuation of sexual violence and—potentially—victims of it.